Analisis Implementasi Food Waste Management: Studi Kasus di Hotel Novotel Jakarta Cikini - Hamiyati; Alfiansyah Mi'raj, Muhamad; Doriza, Shinta (Jurnal Pendidikan dan Perhotelan (JPP), 2023)
This research aims to investigate the phenomenon of food waste and the implementation of food waste management at hotel Novotel Jakarta Cikini, Central Jakarta, as part of their efforts to reduce leftover food waste. The study employs a qualitative descriptive approach. The respondents in this research consist of 5 individuals who are employees of hotel Novotel Jakarta Cikini from various departments directly involved in the food waste management implementation. The research was conducted in June 2023. Data collection techniques included interviews, observations, and documentation.The research findings indicate that the food waste management implemented by hotel Novotel Jakarta CIkini is quite effective, resulting in a reduction of approximately 63 percent in the amount of food waste, from 123 kg per day to around 77.5 kg per day. The food waste management practices at hotel Novotel Jakarta Cikini align with several supporting theories, such as adjusting the size of food portions, processing leftover food materials, donating reprocessed food, and creating organic compost from food waste. Additionally, the study identifies some challenges faced by the hotel employees in educating guests and dealing with internal issues, which have impacted the implementation of food waste management. Furthermore, the research identifies the causes of food waste, ranging from leftover guest meals to unused food ingredients scheduled for processing, as well as the methods employed by hotel Novotel Jakarta Cikini to reduce the accumulation of food waste.